Research on Optimal Scheduling of VPP Based on Latin Hypercube Sampling and K-Means Clustering - Wensi, Cao; Shuo, Wang; Chao, Min; Mingming, Xu (Frontiers in Energy Research, 2022)
Based on a set of classic scenarios, a VPP economic dispatch model is proposed, taking into account the uncertain factors of Wind power and photovoltaic power. First, the basic model of the VPP is analyzed, and then the operating strategy of the VPP is proposed based on the basic model, the impact of the time-of-use electricity price on the economics of the VPP is also considered. A combination of Latin hypercube sampling and K-means clustering is used to generate classic scene sets. At the same time, the model is solved by an algorithm that adds genetic mechanism to the improved particle swarm algorithm(PSO). Finally, according to the established model, a calculation example is used to verify. The design is based on two scenarios of classic scene set and general scene. The optimization configuration results are compared and analyzed. It is confirmed that the VPP optimization configuration under the classic scene set can improve the net income of VPP.